Nitrogen‐Doped Carbon Fibers Embedded with Zincophilic Cu Nanoboxes for Stable Zn‐Metal Anodes. Issue 18 (28th March 2022) - Zeng, Yinxiang; Sun, Peng Xiao; Pei, Zhihao; Jin, Qi; Zhang, Xitian; Yu, Le; Lou, Xiong Wen (David)
Abstract: The practical application of Zn‐metal anodes (ZMAs) is mainly impeded by the limited lifespan and low Coulombic efficiency (CE) resulting from the Zn dendrite growth and side reactions. Herein, a 3D multifunctional host consisting of N‐doped carbon fibers embedded with Cu nanoboxes (denoted as Cu NBs@NCFs) is rationally designed and developed for stable ZMAs. The 3D macroporous configuration and hollow structure can lower the local current density and alleviate the large volume change during the repeated cycling processes. Furthermore, zincophilic Cu and in‐situ‐formed Cu–Zn alloy can act as homogeneous nucleation sites to minimize the Zn nucleation overpotential, further guiding uniform and dense Zn deposition. As a result, this Cu NBs@NCFs host exhibits high CE of Zn plating/stripping for 1000 cycles. The Cu NBs@NCFs–Zn electrode shows low voltage hysteresis and prolonged cycling life (450 h) with dendrite‐free behaviors. As a proof‐of‐concept demonstration, a Zn‐ion full cell is fabricated based on this Cu NBs@NCFs–Zn anode, which demonstrates decent rate capability and improved cycling performance. Abstract : A 3D framework consisting of N‐doped carbon fibers embedded with Cu nanoboxes (Cu NBs@NCFs) is constructed as a multifunctional host for dendrite‐free and stable Zn anodes. Benefiting from the macroporous network, hollow structures, and rich zincophilic sites, the Cu NBs@NCFs host shows low voltage hysteresis, high Coulombic efficiency, and impressive cycling stability in both symmetric and full cells.